PENGARUH PENGGUNAAN ALAT PERAGA MANIPULATIF TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA KELAS VIII SMP SWASTA YAYASAN PERGURUAN KELUARGA PEMATANG SIANTAR - Purba, Ika Rosenta; Purba, Sumarny; Khesarany, Winona (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This study aims to determine the effect of the use of manipulative teaching aids on students' learning motivation in the human respiratory system material of class VIII of SMP Swasta Yayasan Perguruan Keluarga Pematang Siantar. The population in this study was the entire class VIII consisting of 4 classes with a total of 98 students. Sampling was carried out using a purposive sampling technique, namely 2 classes with a total of 50 students. The results of the data analysis showed that the average initial score of the experimental class questionnaire was 45.72 and the average control class was 44.52 and after being given treatment using manipulative teaching aids, the average final questionnaire for the experimental class was 64.08 while the average control class was 59.48. The average pretest value of the experimental class was 48.40 while the pretest of the control class was 49.40. After being given treatment using manipulative teaching aids, the posttest value of the experimental class was 80.60 while the posttest of the control class was 75.40. Based on the test results, the sig.(2-tailed) value was obtained as much as 0.001<0.05 with t count 3.887>t table 1.711 on df 24 and the questionnaire calculation results obtained a sig.(2-tailed) value of 0.023<0.05 with t count 2.684>t table 2.428 on df 24, this shows that Ha is accepted and H0 is rejected. So it can be concluded that there is an influence of the use of manipulative teaching aids on students' learning motivation on the material of the human respiratory system of class VIII students of SMP Swasta Yayasan Perguruan Keluarga Pematang Siantar.